Assessment of e-Wallet System, e-Agricultural Services and Determinants of Cassava Farmers Participation in Off - Farm Activities in Abuja, Nigeria. - Alabi, Olugbenga Omotayo; Oladele, Olugbenga Ayoola; Lawal, Folorunsho Alimi (Journal of Agricultural Sciences (Belgrade), 2016)
Abstract This study assessed e-wallet system (electronic-wallet), e-Agricultural services and determinants of cassava farmers’ participation in off-farm activities in Abuja, Nigeria. A sample of 67 cassava farmers was selected through a multistage sampling technique from six selected agricultural extension blocks. The data were collected with the aid of a questionnaire. The analytical tools used were descriptive statistics and Maximum Likelihood Estimates using Logit regression model. The results indicated that e-wallet is an innovative, motivational mobile technology, the first in sub-Saharan Africa to distribute mobile phones to farmers which bring fertilizer inputs, seed inputs, financial services, and agricultural information tips to farmers; this increase yields and output. The e-wallet system targeted 20 million farmers and to distribute 10 million mobile phones to farmers in 4 years. In 2014, 1000 agro dealers registered on the e-wallet system, 1.2 million farmers have also received inputs via their e – wallet system, while 14.5 million farmers have registered on the e-wallet system. The e – wallet system has had impact to the Nigerian economy which was estimated 30-40 billion dollars to GDP. Furthermore, most of sampled cassava farmers were within the age range of 36-50 years. About 94% of sampled cassava farmers were male. Off – farm income has the potential to improve the income of farmers. The types of off – farm activities participated in by cassava farmers include; teaching, tailoring, hunting, pottery, blacksmithing, petty trading etc. Farmers’ age; farming experience and number of off –farm activities were significant variables influencing farmers’ participation in off – farm activities at ;  and  respectively .The coefficient of Nagelkerket (R2) value was 0.751.The coefficient of Cox and Snell determinant (R2) value was 0.547. The study recommends that government and non- government organizations should introduce innovations, motivations, interventions, policies that improve crop production and support the off – farm sector in order to create job opportunities that poor household can participate and benefit directly.